Bhagyamma Gajawada Letters In Economics - Gajawada, Satish (Advances in Social Sciences Research Journal, 2018)
“Bhagyamma Gajawada Letters In Economics” is the extended version of work titled “Smile Theory of Everything” published in International Proceedings of Economics, Development and Research (IPEDR). Please read the entire paper to understand the “Bhagyamma Gajawada Letters In Economics”.